Określenie przedmiotu działalności spółki z ograniczoną odpowiedzialnością w Polsce i na Ukrainie - Dmytruk, Zlata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The article is aimed at conducting comparative research on the object of the limited liability company in Poland and Ukraine. An attempt was made to establish common solutions for these two European legal systems. The author paid particular attention to the existing difference in the regulation of the determination analyzed. Moreover, in this article, Polish and Ukrainian norms concerning the course of the process of determining the object of activity of the studied type of the company were compared. The author tried to find out if the object of the limited liability company is an obligatory element of an agreement of association. The position presented in the article is the result of the analysis of Polish and Ukrainian law, in particular the Code of Commercial Companies and the Law of Ukraine “On limited and additional liability companies” were subjects of this research, as well as the resulting jurisprudence and doctrine.
Keywords: the object of the limited liability company’s activity; obligatory elements of the status of the limited liability company; Polish commercial law; Ukrainian economic and commercial law